The impact of fuel incentive and improved cook stove on firewood collection in refugees camps in Tanzania: A quasi-experimental research design - Tukae Mbegalo (Cogent Economics & Finance)
The demand for solid fuel (firewood) placed an economic burden on the daily procurement of fuel for cooking by forcibly displaced people. The context rendered the distribution of free improved cook stoves (ICS) unsuccessful. Thus, promoting solid fuel incentives might address health and environmental challenges linked to firewood use. This study aimed to assess the impact of an intervention combining ICS and solid fuel on firewood collection in refugee camps in the Kigoma region of Tanzania. Data were drawn from the 2020 UNHCR energy survey, with a final sample of 329 participants from both baseline and end-line surveys. The study employed propensity score matching (PSM) and difference-in-differences (DID) methods. PSM, including inverse probability weighting (IPW), kernel matching and multivariate distance matching, compared refugees receiving ICS alone with those receiving ICS and solid fuel at the end-line. Covariate balance was tested to ensure valid matching assumptions. The DID method analysed the change in firewood collection frequency between baseline and end-line data. Results indicated that combining ICS with solid fuel reduced the number of firewood collection trips by nearly one per week, representing a 44% decrease. This reduction alleviates the labour-intensive burden on refugees, suggesting potential economic, health, and environmental benefits.